2020
DOI: 10.1038/s41598-020-70482-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the psychological impact of malocclusion in adolescents

Abstract: to study the association between orthodontic treatment need and the psychosocial impact of dental aesthetics in a sample of adolescents, as well as other associated factors. A transversal study was conducted on 1,158 adolescents (12-16 years old) examined at the schools selected for the 2018 epidemiological study on oral health in the Comunidad Valenciana (Spain). The need for orthodontic treatment was determined by DAi and iotn. the psychosocial impact was established by the Psychosocial Impact of Dental Aest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Age did not have a significant effect on the psychosocial impact of the malocclusions of our study participants which is comparable to a study carried out among Spanish adolescents [34]. However, it differs from another study where age was found to play a role in the psychosocial impact that malocclusions had on the study participants [13].…”
Section: Discussionsupporting
confidence: 76%
“…Age did not have a significant effect on the psychosocial impact of the malocclusions of our study participants which is comparable to a study carried out among Spanish adolescents [34]. However, it differs from another study where age was found to play a role in the psychosocial impact that malocclusions had on the study participants [13].…”
Section: Discussionsupporting
confidence: 76%
“…Other studies have already shown the association between malocclusion and social determinants, 6 , 9 , 13 , 26 but not with a contextual variable such as the municipal HDI associated with AOB. The lower municipal HDI results indicate that adolescents living in less affluent cities have a higher chance of being found with AOB.…”
Section: Discussionmentioning
confidence: 85%
“… 1 Although AOB is not expected to have a large population prevalence, this malocclusion may be considered a public health problem due to its consequences on chewing, swallowing, and speech dysfunction. 2 Additionally, this condition may have several effects on daily life, 3 such as decreased quality of life, 4 self-esteem, 5 and psychological 6 , 7 and social 7 consequences. AOB requires challenging treatment 8 ; therefore, preventive measures should avoid malocclusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with family history of malocclusion, stimuli during embryonic period, poor oral habits, poor feeding, and systemic diseases are more likely to be affected with malocclusion [10][11][12][13]. If children with malocclusion can not be managed timely and effectively, it not only affects their oral function and appearance, but also causes mental and psychological disorders, such as depression and anxiety [14][15][16].…”
Section: Background What Is Malocclusion?mentioning
confidence: 99%